1988
DOI: 10.2136/sssaj1988.03615995005200060029x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Effects on Availability of Nitrogen to Corn Following a Winter Green Manure Crop

Abstract: Field studies were conducted in 1984 through 1986 to investigate the release of inorganic N to corn (Zea mays L.) following a winter annual green manure crop of hairy vetch (Vicia villosa Roth) that had either been plowed down to 22 cm (conventional tillage, CT), or killed and left on the surface (no‐till, NT). Soil samples were taken regularly throughout the season at three depths (0–7.5 cm, 7.5–22 cm and 22–45 cm) and analyzed for inorganic N. Crop growth and N uptake, as well as various other plant, soil an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
0
11

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 0 publications
7
51
0
11
Order By: Relevance
“…In addition, because soil-incorporated residues were less prone to desiccation than surficial residues, incorporated residues may have been mineralized more rapidly. Various studies have similarly demonstrated a larger available N supply from soil-incorporated than from surface-applied legume residues (McCalla and Russel 1948;Wilson and Hargrove 1986;Sarrantonio and Scott 1988).…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because soil-incorporated residues were less prone to desiccation than surficial residues, incorporated residues may have been mineralized more rapidly. Various studies have similarly demonstrated a larger available N supply from soil-incorporated than from surface-applied legume residues (McCalla and Russel 1948;Wilson and Hargrove 1986;Sarrantonio and Scott 1988).…”
Section: Mechanismsmentioning
confidence: 99%
“…Tillage has been shown to increase the available N supply from green manure crops compared with herbicide application (Sarrantonio and Scott 1988). However, in field studies with corn, the fertilizer N response following alfalfa was found to be similar whether the previous alfalfa crop had been terminated by herbicide application or by tillage (Triplett et al 1979;Levin et al 1987).…”
mentioning
confidence: 99%
“…Oyer and Touchton (1990) found that inclusion of soybean and clover in cropping systems provided N for corn, and corn yields were greater in rotation than in continuous corn systems. Paré et al (1993a) found only a limited benefit from soybean in rotation with corn in Quebec.The impact of legumes on corn yield and response to N fertilizers may depend on cultivation methods and weather conditions (Sarrantonio and Scott 1988). In a dry year, vetch cover crops contributed much less available N to NT corn than to CT corn, but yield with NT was higher than with CT because of improved water efficiency due to cover crops effects.…”
mentioning
confidence: 99%
“…The impact of legumes on corn yield and response to N fertilizers may depend on cultivation methods and weather conditions (Sarrantonio and Scott 1988). In a dry year, vetch cover crops contributed much less available N to NT corn than to CT corn, but yield with NT was higher than with CT because of improved water efficiency due to cover crops effects.…”
mentioning
confidence: 99%
“…Neste sentido, diversos estudos têm sido realizados, enfocando não só o potencial de plantas de cobertura de ciclo hibernal (Sarrantonio & Scott, 1988;Blevins et al, 1990;Da Ros, 1993;Pavinato et al, 1994;Freitas et al, 1996;Amado et al, 1998), mas também de espécies de ciclo estival (Scherer & Baldissera, 1988;Burle et al, 1992;Wildner & Dadalto, 1992;Araújo & Almeida, 1993;Bayer et al, 1998;Carsky et al, 1998).…”
Section: Introductionunclassified